Ethnozoological uses and local people’s perceptions of a competitor primate in the Fringe of the Kundelungu National Park, D.R. Congo - Kazaba, Paul Kaseya; Mandomombe, Gordon Tinaye; Tshikung, Didier Kambol; Sowunmi, Akindayo Abiodun; Aweto, Albert Orodena (Ethnobiology and Conservation, 2020)
Several studies investigate the human dimension of human-wildlife conflicts, but human attitudes towards forest-dependent animals such as primates in the context of competition for forest resources are still under-researched. We used a semi-structured questionnaire and conducted ethnozoological surveys in order to identify the uses of Kinda baboons (Papio kindae Lönnberg) and the main factors associated with local people’s attitudes towards this frugivorous primate, at the periphery of the Kundelungu National Park, Democratic Republic of Congo. This study indicates that Kinda baboons are important to community members, essentially for consumptive uses, namely as bushmeat and medicinal animals. The association between local peoples’ anti-conservation attitudes towards these baboons and mentions of the depletion of co-used indigenous trees has been confirmed statistically, suggesting the perception of baboons as competitors. Also, even though the majority of respondents recognized the vulnerability of baboons to the depletion of co-used indigenous trees, against our hypothesis, most of them were not inclined to use these resources sustainably. However, an association between the frequency of encounters with Kinda baboons and park-adjacent dwellers’ willingness to conserve baboon-edible trees has been established. We therefore support the view that improving the availability of co-used trees through reforestation or agroforestry is likely to alleviate the prevalence of negative attitudes towards tree-dependent animals. Also, in order to gain community support to protected areas and wildlife, pro-conservation campaigns in similar settings should not merely highlight the vulnerability of animals to the depletion of their resources, but also promote the responsible access of local people to protected areas.